China shock: environmental impacts in Brazil - Dornelas, Victor Simões (2019)
We study whether the \"China shock\'\", defined as China\'s rapid emergence in global markets, caused environmental impacts in Brazilian municipalities, since previous evidence points to effects on real wages and formal sector employment over the period of 2000 to 2010. Building on recent theoretical developments, we implement a shift-share strategy to explore variation in economic specialization between municipalities and find that China\'s direct influence on the deforestation of the Amazon and Cerrado was on average insignificant, which is supported by the literature. On the other hand, China\'s demand for commodities seemed to increase pollution-related mortality of children in mining municipalities, a result obtained by comparing it to mortality caused by other factors. However, we show that this is most likely explained by a municipality\'s degree of specialization in mining activities rather than its exposure to trade with China. We conclude that the environmental effects of the China shock on Brazilian municipalities were small, if not negligible.